Strategy for Structuring Traditional Markets in The Department Of Trade and Industry Of Serang City (Case Study Of Karangantu Traditional Market) - Hudaefah, Hudaefah; Budiati, Ayuning; Maisaroh, Ima (Future Science, 2025)
Structuring traditional markets is an important step to improve infrastructure, governance, and the market environment to make it more orderly, safe, clean, and comfortable for traders and buyers. However, efforts to organise traditional markets in Serang City are still not optimal. One of the markets that needs restructuring is Karangantu Market, which is rundown, narrow, with minimal facilities and poorly maintained. The purpose of this research is to explain the Strategy for Structuring Traditional Markets in the Department of Trade and Industry of Serang City (Case Study of Karangantu Traditional Market). This research uses the theory (Rangkuti, 2021), namely IFAS and EFAS matrix analysis and SWOT matrix analysis consisting of strengths, weaknesses, opportunities, and threats. The results showed that the structuring strategy carried out was not optimal and there was no selection of the right strategy to support the success of market structuring. Therefore, it is recommended that the Department of Trade and Industry of Serang City improve the basic facilities of Margaluyu Market as a relocation location, re-evaluate the relocation location based on accessibility and market potential, conduct integrated and firm supervision and arrangement of street vendors, and develop Karangantu Market into a clean, healthy, and environmentally friendly green market in order to increase the competitiveness of traditional markets